Design and Fluorescence Localization of Lipid‐Rich Domains in Multiphase Coacervate Droplets Based on AIE‐Active Molecules. Issue 2 (17th November 2020) - Jia, Liyan; Ji, Zhen; Ji, Yan‐ming; Zhou, Chengcheng; Xing, Guo‐wen; Qiao, Yan
Abstract: Liquid‐liquid phase separation has been recognized as an approach to realize cellular compartmentalization and create subdivisions of intracellular space into functional membraneless organelles. Multiphase coacervate droplets with complex, nested inner phases as a generic phenomenon are known to be involved in significant biochemical processes and facilitate specific functions. Herein, we present a strategy to develop molecular self‐sorting complexation that leads to the formation of lipid‐rich sub‐compartments in membraneless coacervate microdroplets. We also show the specific localization and visualization of hydrophobic lipid domains within multiphase hydrophilic droplets under a fluorescence microscope by developing a rationally synthesized aggregation‐induced emission (AIE)‐active molecule. The AIE probe with a tetraphenylethylene core and four water‐soluble glucosamine units exhibits high sensitivity and selectivity towards the lipid‐rich microdomains. We anticipate that the design of fluorescently localized self‐sorting liquid droplets will shed light on the research of mimicking multicompartalized organelles and help to understand dynamic reorganization of sub‐divided space in protocell systems. Abstract : All in order : Liquid‐liquid phase separation induced coacervate microdroplets represent promising platforms to elucidate essential features of prebiotic chemical organization and emulate membrane‐less organelles found in living cells. Lipid‐rich sub‐compartments in the multiphase coacervates are constructed and selectively localized by using an AIE‐active molecule. The conformation of organelle‐like coacervate structures sheds light on the research mimicking multicompartalized organelles and helps to understand dynamic reorganization of sub‐divided space in protocell systems.